Bile Acids and the Microbiome: Making Sense of This Dynamic Relationship in Their Role and Management in Crohn's Disease. (22nd March 2022) - Kumar, Aditi; Al-Hassi, Hafid O.; Steed, Helen; Phipps, Oliver; Brookes, Matthew J.
Abstract : Background . Bile acids help maintain the physiological balance of the gut microbiome and the integrity of the intestinal epithelial barrier. Similarly, intestinal bacteria play a major role in bile acid metabolism as they are involved in crucial biotransformation steps in the enterohepatic circulation pathway. Understanding the relationship between bile acid signalling and the gut microbiome in Crohn's disease can help target new and innovative treatment strategies. Aims . This review summarises the relationship between bile acids and the microbiome in Crohn's disease and discusses potential novel therapeutic options. Methods . We performed a literature review on bile acid signalling, its effect on the gut microbiome, and therapeutic applications in Crohn's disease. Results . Current research suggests that there is a strong interplay between the dysregulated microbiota, bile acid metabolism, and the mucosal immune system that can result in a changed immunological function, triggering the inflammatory response in Crohn's disease. Recent studies have demonstrated an association with altering the enterohepatic circulation and activating the farnesoid X receptor signalling pathway with the use of probiotics and faecal microbial transplantation, respectively. Bile acid sequestrants have been shown to have anti-inflammatory, cytoprotective, and anti-apoptotic properties with the potential to alter the intestinal microbial composition, suggesting a possible role in inducing and maintaining Crohn's disease. Conclusions . Active Crohn's disease has been correlated with changes in bacterial concentrations, which may be associated with changes in bile acid modification. Further research should focus on targeting these areas for future therapeutic options.